Multimodal Biometric Authentication System (Trinity Journal of Management, IT & Media (TJMITM), 2012)
A wide variety of applications require reliable and secure  verification schemes to confirm the identity of an individual  requesting authorized accessing to a specified service.  Examples of such applications include secure access to  buildings, personal computer systems, laptops, cellular  phones and ATMs. In the absence of robust verification  schemes, these systems are subject to the tricks of an  impostor. Biometric authentication (BA) is a problem of  verifying an identity claim using a person’s behavioral and  physiological characteristics.
Keywords: Binary classifiers; biometrics; classifier fusion; feature extraction; support vector machine; ROC